SPE Annual Technical Conference and Exhibition 2014
DOI: 10.2118/170912-ms
|View full text |Cite
|
Sign up to set email alerts
|

Global Component Lumping for EOS Calculations

Abstract: To reduce CPU time in compositional reservoir simulations, a minimum number of components should be used in the equation of state (EOS) to describe the fluid phase and volumetric behavior. A "detailed" EOS model often contains from 20 to 40 components, with the first 10 components representing pure compounds H 2 S, CO 2 , N 2 , C 1 , C 2 , C 3 , i-C 4 , n-C 4 , i-C 5 , and n-C 5 . The remaining components represent a split of the heavier C 6ϩ material in single-carbon-number (SCN) fractions such as C 6 , C 7 ,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…In comparison with other methods for lumping, Whitson methods is more accuratly estimate lumping process. For instance, Lee et al (1982) suggest that C 7+ fractions can be grouped into two pseudo-components, which in turn limits the number of pseudo components [9]. What about other correlations, there is also some limitations for lumping, such as the Coats lumping methodology is allows "partial lumping" of original components into several pseudocomponents [9].…”
Section: нефтехимия Table 2 -Lumped Fluid Description By Analytical M...mentioning
confidence: 99%
“…In comparison with other methods for lumping, Whitson methods is more accuratly estimate lumping process. For instance, Lee et al (1982) suggest that C 7+ fractions can be grouped into two pseudo-components, which in turn limits the number of pseudo components [9]. What about other correlations, there is also some limitations for lumping, such as the Coats lumping methodology is allows "partial lumping" of original components into several pseudocomponents [9].…”
Section: нефтехимия Table 2 -Lumped Fluid Description By Analytical M...mentioning
confidence: 99%
“…In the test cases shown later, we will use a 9-component characterization developed by Alavian et al (2014) using a Peng-Robinson EOS. We will use the initial composition corresponding to a low-volatility oil and use a temperature of 200°F.…”
Section: Fluid Modelmentioning
confidence: 99%
“…Joergensen and Stenby (1995) compared 12 different lumping procedures and found that none of these methods were consistently better than the others. Because no approach seems to be better than the others, Alavian et al (2014) suggested using an extensive statistical approach to test for the best lumping among thousands of possible scenarios.…”
Section: Introductionmentioning
confidence: 99%
“…In order to minimize the CPU time in compositional reservoir modeling, the number of the components of the hydrocarbon mixtures in the equation of state (EOS) that provide the fluid phase behavior should be reduced to a reasonable number (Alavian, Whitson, & Martinsen, 2014).…”
Section: Components Lumpingmentioning
confidence: 99%
“…A typical EOS model mostly has 20 to 40 components in which the first 10 components representing pure components such as H2S, CO2, N2, C1, C2, C3, i-C4, n-C4, i-C5, and n-C5. The other components in the EOS model are a split of the heavy components such as single-carbon number (SCN) fractions, C6, C7, C8 and C9, or combinations of SCN fractions such as C10-C12, C13-C19, C20-C29 and C30+ (Alavian, Whitson, & Martinsen, 2014). According to the literature, there is no specific method to choose the optimum lumping scheme that provides precise results similar to the single carbon number results.…”
Section: Components Lumpingmentioning
confidence: 99%